2016
DOI: 10.1186/s12968-017-0370-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of both the area-at-risk and acute myocardial infarct size in ST-segment elevation myocardial infarction using T1-mapping

Abstract: BackgroundA comprehensive cardiovascular magnetic resonance (CMR) in reperfused ST-segment myocardial infarction (STEMI) patients can be challenging to perform and can be time-consuming. We aimed to investigate whether native T1-mapping can accurately delineate the edema-based area-at-risk (AAR) and post-contrast T1-mapping and synthetic late gadolinium (LGE) images can quantify MI size at 1.5 T. Conventional LGE imaging and T2-mapping could then be omitted, thereby shortening the scan duration.MethodsTwenty-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…Indeed, Garg et al demonstrated reliable determination of IS by parametric mapping, even indicating superior diagnostic accuracy of extracellular volume mapping as compared to LGE, which is limited by an overestimation of IS in the acute setting post-STEMI [67]. These results could be corroborated by Bulluck et al [68]; however, these small studies could not validate their findings for hard clinical events, which remains to be done by future studies. Compressed sensing has not only been investigated for accelerating cine CMR imaging but also shortening scan time of LGE imaging [69].…”
Section: Infarct Sizementioning
confidence: 94%
“…Indeed, Garg et al demonstrated reliable determination of IS by parametric mapping, even indicating superior diagnostic accuracy of extracellular volume mapping as compared to LGE, which is limited by an overestimation of IS in the acute setting post-STEMI [67]. These results could be corroborated by Bulluck et al [68]; however, these small studies could not validate their findings for hard clinical events, which remains to be done by future studies. Compressed sensing has not only been investigated for accelerating cine CMR imaging but also shortening scan time of LGE imaging [69].…”
Section: Infarct Sizementioning
confidence: 94%
“…Bulluck and colleagues 43 recently showed that post-contrast T1-mapping can accurately quantify acute MI size in a small group of STEMI patients, obviating the need to perform late gadolinium enhancement imaging. Recent studies have also investigated whether native T1-mapping (pre-contrast) can assess MI size.…”
Section: Recent Advances In the Role Of Cmr In Reperfused Stemi Patientsmentioning
confidence: 99%
“…A comprehensive cardiac magnetic resonance imaging (MRI) scan takes about an hour. 7,8 This may be poorly tolerated by the acute STEMI patients. As IMH invariably occurs in areas of MVO (occurring in 50% of patients), 1 it may not be necessary to perform T 2 * mapping in those without MVO.…”
Section: To the Editormentioning
confidence: 99%